Análise termo-hidráulica preliminar de uma vareta combustível PWR com seção transversal no formato de hemácia sob condições estacionárias - Oliveira, Maria Vitória Aguiar de (2018)
The objective of this work is to compare the temperature distributions between fuel cells with a circular cross-section and those of cross-section in the form of red cells for PWRs. The idea for the work came from the realization that the shape of the red blood cells allows the O2 gases to penetrate to the center of the cell homogeneously and more quickly. The gas diffusion equation in any environment is very similar to the heat diffusion equation (Fick’s Law and Heat Flow, Fourrier’s Law, considering the temperature at the place of the concentration). Previous work compared the shape of solid fuel rods of circular section and section in the red cell format, and showed that the new format improved the heat transfer process, reducing the thermal resistance between the center of the UO2 pellet and the coating. Thus, a significant increase of 23% in the specific power of the reactor was possible. Recent studies have found that 12x12 sets of annular fuel rods can increase the specific power of the reactor by at least 20% when compared to solid ones, without affecting the safety of the reactor. In this work we will study the fuel rods cast with cross sections in red globule format, for this we will analyze the temperature distribution in function of the physical and geometric parameters, comparing with the theoretical results known in the literature on the fuel rods of circular section stationary state. At the end, we concluded there was an improvement in the temperature distribution between the fuel and the coating of the rod without exceeding the temperature limits that guarantee the integrity of these components.